High-strength ductile cast iron and method for producing the same

CN122979741APending Publication Date: 2026-10-27DANDONG LONGSHENG FOUNDRY LTD CO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611468604.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种高强度球墨铸铁及其制备方法,针对现有技术中球墨铸铁制动盘在400~600℃交变热应力工况下,纳米增强相与铁基体之间因缺乏高温稳定的冶金结合界面,导致增强相/Fe界面在热循环中率先脱粘成为疲劳裂纹源,进而造成高温强度不足与热疲劳寿命下降的缺陷

Benefits of technology

[0029](1)本发明中聚多巴胺改性VC@ZrC核壳颗粒表面在铁液中热解生成的碳质界面层,改善了增强相与铁基体的润湿性,降低了颗粒/基体界面的脱粘倾向,从而提高了球墨铸铁的高温强度与抗热疲劳性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979741A_ABST
    Figure CN122979741A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of nodular cast iron preparation, in particular to a high-strength nodular cast iron and a preparation method thereof.In the present application, a polydopamine modified VC@ZrC core-shell particle forms a metallurgical bonding interface with an iron matrix, avoids interface debonding under high-temperature alternating thermal stress, and improves high-temperature strength and thermal fatigue resistance.Ba-Ca-Si@Al2O3 slow-release type inoculant delays the release of active components, and in combination with secondary inoculation, inhibits inoculation recession.The released active components provide heterogeneous nucleation cores for graphite, increase the number of graphite nodules, refine the graphite nodule diameter, improve the spheroidization rate, and improve the graphite organization form.The slow-release type inoculant provides a uniform matrix for the core-shell particle to transfer the load, and the core-shell particle inhibits high-temperature deformation and crack propagation of the matrix through pinning effect;both of them meet the service requirements of heavy commercial vehicle brake discs under repeated thermal cycle conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ductile iron preparation technology, specifically a high-strength ductile iron and its preparation method. Background Technology

[0002] Ductile iron is widely used in the manufacture of key components such as brake discs for heavy-duty commercial vehicles due to its excellent damping, wear resistance, and machinability. Under conditions of long downhill driving or frequent braking, the surface temperature of the brake disc rises sharply to 400-600°C, and then cools rapidly after braking. This repeated thermal cycle generates enormous alternating thermal stress within the material, ultimately leading to the initiation and propagation of thermal fatigue cracks.

[0003] For brake discs, the initiation of thermal fatigue cracks is closely related to the material's strength level—the lower the material strength at high temperatures, the easier it is for local plastic deformation to accumulate under thermal stress, thus accelerating crack initiation. Therefore, improving the high-temperature strength of ductile iron is a key prerequisite for suppressing thermal fatigue cracking. Adding nano-ceramic particles to ductile iron is one way to improve its strength. Chinese patent document CN201911086023.8 discloses a method for reinforcing ductile iron materials using nano-SiO2 particles. This involves preparing a SiO2 / Fe master alloy by surface-plating the nano-SiO2 particles with copper and then adding it to molten iron to refine the grains and improve the strength and plasticity of the ductile iron material. Chinese patent document CN202110406625.8 discloses a method for reinforcing ductile iron materials using nano-Ti2O3 ceramic particles. This involves surface-plating the nano-Ti2O3 ceramic particles with nickel and then adding them to molten iron to improve the strength of the ductile iron material.

[0004] While the aforementioned existing technologies have improved the dispersion and flotation of nanoparticles in molten iron to some extent through surface coating modification, the coating metal (Cu or Ni) only undergoes limited physical wetting or miscibility with the molten iron, failing to establish a high-temperature stable metallurgical interface between the reinforcing phase and the iron matrix. Under alternating thermal stress at 400–600°C, the bonding strength of the reinforcing phase / Fe interface is insufficient, the load cannot be effectively transferred, and the interface is prone to debonding, becoming a fatigue crack initiation point. Consequently, the reinforcing effect of the nanoparticles is not fully utilized, and the high-temperature strength and thermal fatigue resistance of the material still cannot meet service requirements. Summary of the Invention

[0005] (1) Technical problems to be solved

[0006] The purpose of this invention is to provide a high-strength ductile iron and its preparation method. In the prior art, under alternating thermal stress conditions of ductile iron brake discs at 400~600℃, the lack of a high-temperature stable metallurgical bonding interface between the nano-reinforcing phase and the iron matrix leads to the reinforcing phase / Fe interface debonding first during thermal cycling, becoming a fatigue crack initiation, and thus causing insufficient high-temperature strength and reduced thermal fatigue life.

[0007] (2) Technical solution

[0008] To achieve the above objectives, on the one hand, the present invention provides a high-strength ductile iron, which is composed of the following elemental composition by weight percentage: C 3.4~3.8%, Si 2.2~2.8%, Mn 0.3~0.6%, Mg 0.03~0.06%, Ce 0.0058~0.0174%, La 0.0027~0.0081%, Pr 0.0015~0.0045%, P ≤0.05%, S ≤0.03%, with the balance being iron and unavoidable impurities;

[0009] Based on the total mass of the above-mentioned elements, it also includes 0.05%~0.50% polydopamine-modified VC@ZrC core-shell particles and 0.01%~0.10% Ba-Ca-Si@Al2O3 sustained-release inoculant.

[0010] Furthermore, the preparation method of the polydopamine-modified VC@ZrC core-shell particles includes the following steps:

[0011] A1. Disperse VC nanoparticles in deionized water to obtain a VC suspension; dissolve zirconium oxychloride in deionized water to obtain a zirconium salt solution; then add the zirconium salt solution to the VC suspension; add ammonia water dropwise to adjust the pH, stir and age to obtain precursor suspension A; add glucose to precursor suspension A, evaporate and concentrate, and dry to obtain precursor powder A.

[0012] A2. Precursor powder A was placed in a tube furnace and heated under an inert atmosphere. After cooling with the furnace, a sintered product was obtained. The sintered product was ball-milled and then oxidized in air. It was then washed with deionized water and anhydrous ethanol and dried to obtain purified VC@ZrC core-shell particles.

[0013] A3. The purified VC@ZrC core-shell particles were dispersed in tris(hydroxymethyl)aminomethane-hydrochloric acid buffer; dopamine hydrochloride was added, and the mixture was stirred and reacted; the mixture was centrifuged, washed with deionized water, and finally dried to obtain polydopamine-modified VC@ZrC core-shell particles.

[0014] Further, the average particle size of the VC nanoparticles is 50~200nm; the mass ratio of zirconium oxychloride to VC nanoparticles is 0.6:1; the mass ratio of glucose to VC nanoparticles is 0.55:1; the solid-liquid ratio of the purified VC@ZrC core-shell particles to the tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution is 1g:200mL; and the mass ratio of dopamine hydrochloride to VC@ZrC core-shell particles is 0.1:1.

[0015] Furthermore, the preparation method of the Ba-Ca-Si@Al2O3 sustained-release inoculant includes the following steps:

[0016] B1. Disperse Ba-Ca-Si inoculant particles in anhydrous ethanol to obtain a Ba-Ca-Si suspension; dissolve aluminum isopropoxide in anhydrous isopropanol to obtain an aluminum alkoxide solution; then add the aluminum alkoxide solution to the Ba-Ca-Si suspension; add deionized water dropwise, and age to obtain precursor suspension B.

[0017] B2. Filter the precursor suspension B, wash the filter cake with deionized water, and dry it to obtain precursor powder B;

[0018] B3. The precursor powder B was calcined and cooled in the furnace to obtain Ba-Ca-Si@Al2O3 slow-release inoculant.

[0019] Further, the Ba-Ca-Si inoculant particles are composed of the following weight percentages: Si 60~70%, Ba 4~8%, Ca 1~3%, Al 0.5~1.5%, with the balance being Fe; the average particle size of the Ba-Ca-Si inoculant particles is 0.2~1mm; and the mass ratio of aluminum isopropoxide to Ba-Ca-Si inoculant particles is 0.1:1.

[0020] Furthermore, the method for preparing a high-strength ductile iron includes the following steps:

[0021] C1. Preparation of reinforced phase cored wire: Polydopamine-modified VC@ZrC core-shell particles are spread on the surface of low carbon steel foil, rolled and pressed to obtain strip-shaped reinforced phase cored wire;

[0022] C2. Raw material smelting: Pig iron, scrap steel, ferrosilicon, and ferromanganese are batched according to the target composition and then added to a medium-frequency induction furnace for smelting. Slag is removed to obtain raw molten iron.

[0023] C3. Spheroidizing treatment and primary inoculation treatment: The original molten iron is transferred into a spheroidizing ladle and the ladle is covered; spheroidizing agent and inoculant A are added and charged, and the molten iron is poured in to complete the spheroidizing and primary inoculation treatment, and the molten iron after spheroidizing and inoculation treatment is obtained;

[0024] C4. Addition of reinforcing phase and secondary inoculation treatment: Transfer the molten iron after spheroidizing inoculation treatment into a ladle, heat it to 1450~1460℃, then add strip-shaped reinforcing phase cored wire and Ba-Ca-Si@Al2O3 slow-release inoculant, stir, and let it stand to obtain molten iron;

[0025] C5. Casting: Molten iron is poured into a sand mold, cooled, and cleaned to obtain high-strength ductile iron.

[0026] Furthermore, the thickness of the low-carbon steel foil is 0.1~0.3mm; the mass ratio of the low-carbon steel foil to the polydopamine-modified VC@ZrC core-shell particles is 5:1.

[0027] Further, the spheroidizing agent is composed of 5-10% Mg, 1.0%-2.8% Ce, 0.5%-1.3% La, 0.25%-0.7% Pr, 1-3% Ca, 35-50% Si, and the balance Fe; the amount of the spheroidizing agent added is 1.2% of the total mass of the original molten iron; the inoculant A is composed of 65-75% Si, 1.0-3.0% Ca, 0.5-1.5% Al, and the balance Fe; the amount of the inoculant A added is 0.5% of the total mass of the original molten iron.

[0028] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0029] (1) In this invention, the carbonaceous interface layer generated on the surface of polydopamine-modified VC@ZrC core-shell particles by pyrolysis in molten iron improves the wettability of the reinforcing phase and the iron matrix, reduces the tendency of particle / matrix interface to debond, thereby improving the high temperature strength and thermal fatigue resistance of ductile iron.

[0030] (2) In this invention, the Ba-Ca-Si@Al2O3 slow-release inoculant not only slows down the release rate of the active inoculant components, but also effectively inhibits the inoculant decay in combination with secondary inoculant. The released active components such as Ca also act as the heterogeneous nucleation core of graphite, promote the refinement of graphite spheres and the improvement of spheroidization rate, make the graphite structure smaller and more dispersed, and further improve the mechanical properties of the material.

[0031] (3) The Ba-Ca-Si@Al2O3 slow-release inoculant and the polydopamine modified VC@ZrC core-shell particles form a synergistic effect through the action chain of "matrix structure protection → effective load transfer → high temperature deformation inhibition", which enables the material of the present invention to meet the service requirements of heavy commercial vehicle brake discs under repeated thermal cycling conditions. Attached Figure Description

[0032] Figure 1 This is a flowchart illustrating the preparation process of the high-strength ductile iron of this invention. Detailed Implementation

[0033] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0034] Example 1: This example discloses a high-strength ductile iron, which is composed of the following elemental composition by weight percentage: C 3.6%, Si 2.5%, Mn 0.45%, Mg 0.045%, Ce 0.0116%, La 0.0054%, Pr 0.0030%, P 0.03%, S 0.02%, with the balance being iron and unavoidable impurities;

[0035] Based on the total mass of the above-mentioned elements, it also includes 0.28% polydopamine-modified VC@ZrC core-shell particles and 0.055% Ba-Ca-Si@Al2O3 sustained-release inoculant.

[0036] The preparation method of the polydopamine-modified VC@ZrC core-shell particles includes the following steps:

[0037] A1. Add 100g of VC nanoparticles to 1000mL of deionized water and sonicate for 15 minutes to obtain a VC suspension; dissolve 60g of zirconium oxychloride in 300mL of deionized water to obtain a zirconium salt solution; then add the zirconium salt solution to the VC suspension and stir evenly; then add 5% ammonia water to adjust the pH of the system to 9-10, continue stirring for 30 minutes to age, and obtain precursor suspension A; add 55g of glucose to precursor suspension A, stir until completely dissolved, then evaporate and concentrate in an 80℃ water bath, and dry at 100℃ for 5 hours to obtain precursor powder A;

[0038] A2. Precursor powder A was placed in a graphite tube furnace and heated to 1580℃ at 5℃ / min under the protection of flowing argon (flow rate 0.5L / min), held for 1.2 hours, and cooled to room temperature with the furnace to obtain the sintered product. The sintered product was placed in a planetary ball mill and ball-milled at 350rpm for 1.5 hours for mild depolymerization. The depolymerized powder was placed in a muffle furnace and subjected to controlled oxidation treatment at 280℃ for 30-40 minutes in an air atmosphere. It was then washed three times with deionized water (1000mL each time) and once with anhydrous ethanol (500mL). Finally, it was dried at 80℃ for 6 hours to obtain purified VC@ZrC core-shell particles.

[0039] A3. Take 40g of purified VC@ZrC core-shell particles and disperse them in 8000mL of 10mmol / L tris(hydroxymethyl)aminomethane-hydrochloric acid buffer (pH=8.5), sonicate for 15 minutes; then add 4g of dopamine hydrochloride, stir at room temperature in the dark for 24 hours; centrifuge at 8000rpm for 15 minutes, wash three times with deionized water (300mL each time), and finally vacuum dry at 60℃ for 12 hours to obtain polydopamine-modified VC@ZrC core-shell particles.

[0040] The average particle size of the VC nanoparticles is 50~200nm.

[0041] The preparation method of the Ba-Ca-Si@Al2O3 sustained-release inoculant includes the following steps:

[0042] B1. Disperse 20g of Ba-Ca-Si inoculant particles in 400mL of anhydrous ethanol and stir until homogeneous to obtain a Ba-Ca-Si suspension; separately dissolve 2.0g of aluminum isopropoxide in 50mL of anhydrous isopropanol to obtain an aluminum alkoxide solution; then add the aluminum alkoxide solution to the Ba-Ca-Si suspension and stir until homogeneous; then add 1.0~1.5mL of deionized water dropwise, continue stirring for 30 minutes and age to obtain precursor suspension B;

[0043] B2. Filter the precursor suspension B, wash the filter cake with deionized water 3 times (400 mL each time), and dry it at 80°C for 6 hours to obtain precursor powder B.

[0044] B3. Precursor powder B is placed in a muffle furnace and heated to 500°C at 5°C / min under air atmosphere. The temperature is maintained for 2 hours and then cooled to room temperature with the furnace to obtain Ba-Ca-Si@Al2O3 slow-release inoculant.

[0045] The Ba-Ca-Si inoculant particles are composed of the following weight percentages: Si 65%, Ba 6%, Ca 2%, Al 1.0%, with the balance being Fe; the average particle size of the Ba-Ca-Si inoculant particles is 0.2~1mm.

[0046] A method for preparing high-strength ductile iron includes the following steps:

[0047] C1. Preparation of reinforced phase cored wire: Polydopamine-modified VC@ZrC core-shell particles are evenly spread on the surface of low carbon steel foil, continuously rolled and folded along the length direction to cover and continuously rolled and closed to form a strip-shaped reinforced phase cored wire;

[0048] C2. Raw material smelting: Pig iron, scrap steel, ferrosilicon and ferromanganese are batched according to the target composition and then added to a medium frequency induction furnace for smelting. The smelting temperature is controlled at 1520~1550℃. After the furnace charge is completely melted, the slag is removed to obtain the raw molten iron.

[0049] C3. Spheroidizing and primary inoculation treatment: The original molten iron is transferred into a spheroidizing ladle, and the temperature of the molten iron is controlled at 1400~1450℃ using the ladle cover method. The molten iron is loaded in the order of spheroidizing agent at the bottom, inoculant A at the top, and iron filings on the top layer. The molten iron is then poured in to complete the spheroidizing and primary inoculation treatment, and the molten iron after spheroidizing and inoculation treatment is obtained.

[0050] C4. Addition of reinforcing phase and secondary inoculation treatment: The molten iron after spheroidizing inoculation treatment is transferred into a ladle equipped with a medium frequency induction heat preservation device, and the molten iron is heated to 1450~1460℃ by electric heating; the strip reinforcing phase cored wire is fed into the molten iron by cored wire feeding method, and Ba-Ca-Si@Al2O3 slow-release inoculant is added at the same time, and weak stirring with argon blowing or electromagnetic stirring is carried out for 5 minutes by bottom permeable brick, and then it is allowed to stand for 3 minutes;

[0051] C5. Casting: Molten iron is poured into a sand mold, with the pouring temperature controlled at 1380~1420℃. After cooling and cleaning, high-strength ductile iron is obtained. Figure 1 This is a flowchart illustrating the preparation process of the high-strength ductile iron of this invention.

[0052] The thickness of the low-carbon steel foil is 0.1~0.3mm; the mass ratio of the low-carbon steel foil to the polydopamine-modified VC@ZrC core-shell particles is 5:1.

[0053] The spheroidizing agent is composed of 8% Mg, 1.9% Ce, 0.9% La, 0.5% Pr, 2% Ca, 42% Si, and the balance Fe; the amount of the spheroidizing agent added is 1.2% of the total mass of the original molten iron; the inoculant A is composed of 70% Si, 2.0% Ca, 1.0% Al, and the balance Fe; the amount of the inoculant A added is 0.5% of the total mass of the original molten iron.

[0054] Example 2: This example is based on Example 1, but differs from Example 1 in that it is composed of the following elemental composition by weight percentage: C 3.4%, Si 2.2%, Mn 0.3%, Mg 0.03%, Ce 0.0058%, La 0.0027%, Pr 0.0015%, P 0.01%, S 0.01%, with the balance being iron and unavoidable impurities;

[0055] Based on the total mass of the above-mentioned elements, it also includes 0.05% polydopamine-modified VC@ZrC core-shell particles and 0.01% Ba-Ca-Si@Al2O3 sustained-release inoculant.

[0056] The Ba-Ca-Si inoculant particles are composed of the following weight percentages: Si 60%, Ba 4%, Ca 1%, Al 0.5%, with the balance being Fe.

[0057] The spheroidizing agent is composed of 5% Mg, 1.0% Ce, 0.5% La, 0.25% Pr, 1% Ca, 35% Si, and the balance Fe; the inoculant A is composed of 65% Si, 1.0% Ca, 0.5% Al, and the balance Fe.

[0058] The other components and preparation methods are the same as in Example 1.

[0059] Example 3: This example is based on Example 1, but differs from Example 1 in that it is composed of the following elemental composition by weight percentage: C 3.8%, Si 2.8%, Mn 0.6%, Mg 0.06%, Ce 0.0174%, La 0.0081%, Pr 0.0045%, P 0.05%, S 0.03%, with the balance being iron and unavoidable impurities;

[0060] Based on the total mass of the above-mentioned elements, it also includes 0.50% polydopamine-modified VC@ZrC core-shell particles and 0.10% Ba-Ca-Si@Al2O3 sustained-release inoculant.

[0061] The Ba-Ca-Si inoculant particles are composed of the following weight percentages: Si 70%, Ba 8%, Ca 3%, Al 1.5%, with the balance being Fe.

[0062] The spheroidizing agent is composed of 10% Mg, 2.8% Ce, 1.3% La, 0.7% Pr, 3% Ca, 50% Si, and the balance Fe; the inoculant A is composed of 75% Si, 3.0% Ca, 1.5% Al, and the balance Fe.

[0063] The other components and preparation methods are the same as in Example 1.

[0064] Comparative Example 1: This comparative example is based on Example 1, but differs from Example 1 in that the polydopamine-modified VC@ZrC core-shell particles in this comparative example are not modified with polydopamine, that is, they are only VC@ZrC core-shell particles.

[0065] The other components and preparation methods are the same as in Example 1.

[0066] Comparative Example 2: This comparative example is based on Example 1, but differs from Example 1 in that pure VC nanoparticles are used instead of polydopamine-modified VC@ZrC core-shell particles.

[0067] The other components and preparation methods are the same as in Example 1.

[0068] Comparative Example 3: This comparative example is based on Example 1, but differs from Example 1 in that pure ZrC nanoparticles are used instead of polydopamine-modified VC@ZrC core-shell particles.

[0069] The other components and preparation methods are the same as in Example 1.

[0070] Comparative Example 4: This comparative example is based on Example 1, but differs from Example 1 in that Ba-Ca-Si inoculant particles are used instead of Ba-Ca-Si@Al2O3 sustained-release inoculant in this comparative example.

[0071] The other components and preparation methods are the same as in Example 1.

[0072] Comparative Example 5: This comparative example is based on Example 1, but differs from Example 1 in that physically mixed Ba-Ca-Si particles and Al2O3 powder are used instead of Ba-Ca-Si@Al2O3 slow-release inoculant.

[0073] The other components and preparation methods are the same as in Example 1.

[0074] Comparative Example 6: This comparative example is based on Example 1, but unlike Example 1, no polydopamine-modified VC@ZrC core-shell particles are added in this comparative example.

[0075] The other components and preparation methods are the same as in Example 1.

[0076] Comparative Example 7: This comparative example is based on Example 1, but unlike Example 1, no Ba-Ca-Si@Al2O3 sustained-release inoculant is added in this comparative example.

[0077] The other components and preparation methods are the same as in Example 1.

[0078] Comparative Example 8: This comparative example is based on Example 1, but unlike Example 1, it does not contain polydopamine-modified VC@ZrC core-shell particles and Ba-Ca-Si@Al2O3 sustained-release inoculant.

[0079] The other components and preparation methods are the same as in Example 1.

[0080] Experimental verification:

[0081] For each group of Y2-type test blocks specified in the casting standard GB / T 1348-2019 for Examples 1-3 and Comparative Examples 1-8, tensile test bar blanks with a diameter of 25mm were cut from the center of the test block body in the direction of wall thickness, on the same side as the gating and riser. The sampling was carried out by wire cutting to ensure that the sampling position was consistent and to eliminate the difference in wall thickness effect.

[0082] 1. Room temperature tensile properties:

[0083] Perform the test according to GB / T 228.1-2021 "Metallic materials, tensile testing—Part 1: Test at room temperature". Measure the diameter at three locations—at both ends and the middle of the gauge length—using a micrometer, and take the arithmetic mean as the original diameter d0, accurate to 0.01 mm. Calculate the original cross-sectional area: Original cross-sectional area: = = Mount the specimen in the upper and lower clamps of the universal testing machine, ensuring the specimen axis is aligned with the loading direction. Set the loading rate: 6~60 MPa / s for the elastic stress rate, and 0.00025~0.0025 / s for the strain rate after yielding. Start the testing machine and load until the specimen fractures, recording the maximum force F and the yield force F. 0.2 Carefully butt the fractured specimens and measure the gauge length L after fracture. u .

[0084] Calculation formula:

[0085] Room temperature tensile strength: ;

[0086] Yield strength: ;

[0087] Elongation after fracture: ;

[0088] In the formula, This is the original gauge length (mm).

[0089] 2.500℃ high temperature tensile properties:

[0090] Perform the test according to GB / T 228.2-2015 "Metallic materials, tensile testing—Part 2: High-temperature test method". Place the specimen in a high-temperature tensile fixture, heat to 500±5℃ at a rate ≤10℃ / min, hold for 10 min, and then apply the load. Record the maximum force F after the specimen fractures. 500 Calculate the high-temperature tensile strength: High-temperature tensile strength: .

[0091] 3.500℃ thermal fatigue performance:

[0092] Three thermal fatigue specimens (30×24×15mm, V-notch depth 0.5~1.0mm) were processed in each group. The original notch root condition of each specimen was measured and recorded using a reading microscope (ensuring no original cracks). The resistance furnace was heated to 500±8℃, and the water bath was filled and the temperature controlled at 25±5℃. The specimens were suspended by stainless steel wire and placed in the furnace insulation zone, and the holding time was started for 90 seconds. After the holding time, the specimens were quickly removed by the lifting mechanism and placed in the 25±5℃ water bath for cooling for 10 seconds. The specimens were then removed and the surface moisture was dried with compressed air; this constituted one cycle. The above heating-cooling cycle was repeated for a total of 200 cycles. After the cycle, the length of the main crack initiating at the notch root was measured using a reading microscope. If cracks initiated from both sides of the notch, the longer one was taken as the main crack.

[0093] Calculation formula:

[0094] Crack suppression rate: ;

[0095] In the formula, The average principal crack length (mm) is for Comparative Example 8 (blank control group). The average principal crack length (mm) is the value to be measured.

[0096] 4. Determination of particle mechanical residue rate (acid dissolution-heavy liquid separation method):

[0097] (1) Take metal samples from near the fracture surface of the specimens after room temperature tensile tests in Examples 1-3 and Comparative Examples 1-8, and cut them into pieces with a particle size <2mm. Weigh 20.0000g for each sample (accurate to 0.0001g).

[0098] (2) Place the crushed sample in a 300 mL beaker and slowly add 200 mL of hydrochloric acid. After the violent reaction stops, place the beaker in an ultrasonic cleaner (150 W power, 40 kHz frequency) and ultrasonically vibrate at 25 °C for 30 min until the matrix is ​​completely dissolved. Stir with a glass rod every 5 min during this period.

[0099] (3) Connect the pre-weighed G6 sintered sand funnel (pore size 2~3μm or less) to a vacuum filtration flask and perform vacuum filtration under reduced pressure. Wash the filter residue 8 times (about 25mL each time) with about 200mL of warm deionized water (about 40℃). Then wash twice with about 50mL of anhydrous ethanol.

[0100] (4) Dry the sand core funnel with filter residue at 105°C to constant weight (the difference between two adjacent weighings ≤ 0.0005g). After cooling to room temperature in a desiccator, weigh it.

[0101] (5) Transfer the filter residue from the sintered glass funnel into a 50 mL centrifuge tube. Add approximately 15 mL of diiodomethane and shake thoroughly for 1–2 min. Place the centrifuge tube in a centrifuge and centrifuge at 3000 rpm for 10 min. After centrifugation, the upper floating matter is graphite, and the bottom sediment is ceramic particles. Carefully remove the upper floating graphite matter (along with some of the heavy liquid) with a pipette. Add approximately 10 mL of fresh diiodomethane to the precipitate, shake and centrifuge again, and repeat the purification process twice until the upper solution is clear and free of black graphite suspension.

[0102] (6) Wash the bottom sediment three times with about 30 mL of anhydrous ethanol (10 mL each time), transfer it to a pre-weighed weighing bottle, dry it at 80 °C to constant weight, and weigh it to obtain the mass of the recovered ceramic particles. .

[0103] Calculation formula:

[0104] Theoretical particle mass: ;

[0105] In the formula: It is 20.0000g; The percentage (%) is the mass fraction (%) of polydopamine-modified VC@ZrC core-shell particles (and their substituted particles in the comparative example) in the component.

[0106] Particle recovery rate: ;

[0107] Particle shedding rate: .

[0108] 5. Graphite microstructure and spheroidization rate detection:

[0109] The metallographic examination of ductile iron was performed according to GB / T 9441-2021. Metallographic specimens (Φ15×15mm) were cut from the same location as the mechanical property specimens, and then mounted, pre-ground, and polished to a mirror finish. The graphite morphology was observed using a stereomicroscope at 100x magnification, and the spheroidization rate was assessed according to the GB / T 9441-2021 standard rating chart. The number of graphite spheres per unit area (at least 5 fields of view as specified in the standard) was counted at 500x magnification, and the average number of graphite spheres (number / mm²) was calculated. 2 At the same time, measure the diameter of no less than 50 graphite spheres, calculate the average diameter, and evaluate the sphere diameter grade.

[0110] Table 1. Mechanical properties and thermal fatigue test results:

[0111]

[0112] Table 2. Results of interface detachment rate and graphite microstructure test:

[0113]

[0114] Tables 1 and 2 show that polydopamine modification improves interfacial wettability, while its absence leads to decreased strength and increased shedding rate. The shedding rate of single VC or ZrC particles is higher than that of core-shell particles, confirming the necessity of core-shell synergy. The absence of the Al2O3 shell reduces the thermal fatigue crack inhibition rate, confirming its sustained-release effect. The active components released by the Ba-Ca-Si@Al2O3 sustained-release inoculant provide heterogeneous nucleation cores for graphite, refining graphite spheres and improving sphericity. Only through the synergy of polydopamine-modified VC@ZrC core-shell particles and the Ba-Ca-Si@Al2O3 sustained-release inoculant can excellent room-temperature strength, high-temperature strength, and thermal fatigue resistance be simultaneously obtained.

[0115] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, and improvements made by those skilled in the art within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A high-strength ductile iron, characterized in that, It is composed of the following elements by weight percentage: C 3.4~3.8%, Si 2.2~2.8%, Mn 0.3~0.6%, Mg 0.03~0.06%, Ce 0.0058~0.0174%, La 0.0027~0.0081%, Pr 0.0015~0.0045%, P ≤0.05%, S ≤0.03%, with the balance being iron and unavoidable impurities; Based on the total mass of the above-mentioned elements, it also includes 0.05%~0.50% polydopamine-modified VC@ZrC core-shell particles and 0.01%~0.10% Ba-Ca-Si@Al2O3 sustained-release inoculant.

2. The high-strength ductile iron according to claim 1, characterized in that, The preparation method of the polydopamine-modified VC@ZrC core-shell particles includes the following steps: A1. Disperse VC nanoparticles in deionized water to obtain a VC suspension; dissolve zirconium oxychloride in deionized water to obtain a zirconium salt solution; then add the zirconium salt solution to the VC suspension; add ammonia water dropwise to adjust the pH, stir and age to obtain precursor suspension A; add glucose to precursor suspension A, evaporate and concentrate, and dry to obtain precursor powder A. A2. Precursor powder A was placed in a tube furnace and heated under an inert atmosphere. After cooling with the furnace, a sintered product was obtained. The sintered product was ball-milled and then oxidized in air. It was then washed with deionized water and anhydrous ethanol and dried to obtain purified VC@ZrC core-shell particles. A3. The purified VC@ZrC core-shell particles were dispersed in tris(hydroxymethyl)aminomethane-hydrochloric acid buffer; dopamine hydrochloride was added, and the mixture was stirred and reacted; the mixture was centrifuged, washed with deionized water, and finally dried to obtain polydopamine-modified VC@ZrC core-shell particles.

3. The high-strength ductile iron according to claim 2, characterized in that, The average particle size of the VC nanoparticles is 50-200 nm; the mass ratio of zirconium oxychloride to VC nanoparticles is 0.6:1; the mass ratio of glucose to VC nanoparticles is 0.55:1; the solid-liquid ratio of the purified VC@ZrC core-shell particles to the tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution is 1 g:200 mL; and the mass ratio of dopamine hydrochloride to VC@ZrC core-shell particles is 0.1:

1.

4. The high-strength ductile iron according to claim 1, characterized in that, The preparation method of the Ba-Ca-Si@Al2O3 sustained-release inoculant includes the following steps: B1. Disperse Ba-Ca-Si inoculant particles in anhydrous ethanol to obtain a Ba-Ca-Si suspension; dissolve aluminum isopropoxide in anhydrous isopropanol to obtain an aluminum alkoxide solution; then add the aluminum alkoxide solution to the Ba-Ca-Si suspension; add deionized water dropwise, and age to obtain precursor suspension B. B2. Filter the precursor suspension B, wash the filter cake with deionized water, and dry it to obtain precursor powder B; B3. The precursor powder B was calcined and cooled in the furnace to obtain Ba-Ca-Si@Al2O3 slow-release inoculant.

5. A high-strength ductile iron according to claim 4, characterized in that, The Ba-Ca-Si inoculant particles are composed of the following weight percentages: Si 60~70%, Ba 4~8%, Ca 1~3%, Al 0.5~1.5%, with the balance being Fe; the average particle size of the Ba-Ca-Si inoculant particles is 0.2~1mm; the mass ratio of aluminum isopropoxide to Ba-Ca-Si inoculant particles is 0.1:

1.

6. A method for preparing high-strength ductile iron, applied to the preparation of a high-strength ductile iron as described in any one of claims 1 to 5, characterized in that, The method includes the following steps: C1. Preparation of reinforced phase cored wire: Polydopamine-modified VC@ZrC core-shell particles are spread on the surface of low carbon steel foil, rolled and pressed to obtain strip-shaped reinforced phase cored wire; C2. Raw material smelting: Pig iron, scrap steel, ferrosilicon, and ferromanganese are batched according to the target composition and then added to a medium-frequency induction furnace for smelting. Slag is removed to obtain raw molten iron. C3. Spheroidizing treatment and primary inoculation treatment: The original molten iron is transferred into a spheroidizing ladle and the ladle is covered; spheroidizing agent and inoculant A are added and charged, and the molten iron is poured in to complete the spheroidizing and primary inoculation treatment, and the molten iron after spheroidizing and inoculation treatment is obtained; C4. Addition of reinforcing phase and secondary inoculation treatment: Transfer the molten iron after spheroidizing inoculation treatment into a ladle, heat it to 1450~1460℃, then add strip-shaped reinforcing phase cored wire and Ba-Ca-Si@Al2O3 slow-release inoculant, stir, and let it stand to obtain molten iron; C5. Casting: Molten iron is poured into a sand mold, cooled, and cleaned to obtain high-strength ductile iron.

7. The method for preparing high-strength ductile iron according to claim 6, characterized in that, The thickness of the low-carbon steel foil is 0.1~0.3mm; the mass ratio of the low-carbon steel foil to the polydopamine-modified VC@ZrC core-shell particles is 5:

1.

8. The method for preparing high-strength ductile iron according to claim 6, characterized in that, The spheroidizing agent is composed of 5-10% Mg, 1.0-2.8% Ce, 0.5-1.3% La, 0.25-0.7% Pr, 1-3% Ca, 35-50% Si, and the balance Fe; the amount of the spheroidizing agent added is 1.2% of the total mass of the original molten iron; the inoculant A is composed of 65-75% Si, 1.0-3.0% Ca, 0.5-1.5% Al, and the balance Fe; the amount of the inoculant A added is 0.5% of the total mass of the original molten iron.

Citation Information

Patent Citations

  • Method for reinforcing nodular cast iron materials by utilizing nano SiO2 particles

    CN110629106A

  • A method for reinforcing ductile iron materials using nano-Ti2O3 ceramic particles

    CN113106325B